Theoretical verification of using the Ga-doped ZnO as a charge transport layer in an inorganic perovskite solar cell - Ahmed S.; Akhtaruzzaman M.; Zulhafizhazuan W.; Yusoff Y.; Alnaser I.A.; Karim M.R.; Shahiduzzaman M.; Sobayel K. (Institute of Physics, 2024)
The study encompasses the idea to employ a single bandgap-graded transport layer in lieu of two different (transparent conducting oxide and electron transport layer) layers in the perovskite solar cell to increase the overall device functionality. Numerical simulation has been used to investigate the cell performance parameters. The thickness of the absorber layer has been altered in relation to the defect density to identify the optimal cell parameter values. Maximum power conversion efficiency (PCE) has been recorded as 22.17% at 1E13 cm?3 defect density in the absorber. These findings demonstrate the numerical modeling limitations for the relationship between defect mechanism and performance. The activation energy and effects of series resistance (R s) on solar cells have also been assessed. The temperature degradation gradient of the proposed structure GZO/CsGeI3/NiO/Au has been found to be 3% only with a PCE of 22.17%, which validates the concept of using a bandgap-graded transport layer and paves the way for a new era for perovskite research. 2023 The Japan Society of Applied Physics.